(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This description of the quality of life today for women begins with information on indicators such as income, population, refugees, percent women in political office or boardrooms. The goal for civil society is defined as the survival of the Earth without which other concerns are tangential. The key to effective policies is to measure the cause and effects of environmental degradation and find ways to provide feedback to the decision-makers and ourselves to change behavior. Better quality of life for women means improvement for children and men to any assessment of the quality of life women has to start from the social framework, social structures, cultural norms and value system that influence, social exceptions regarding the behavior of both men and women and determine women’s roles and their positions in the society. A society is composed of many institutions and most important of them are the system of decent family and kinship, marriage and religious traditions. They provide the ideology and the moral basis for men and women about their rights and duties and their status and role.